2017
DOI: 10.1891/0886-6708.vv-d-16-00079
|View full text |Cite
|
Sign up to set email alerts
|

Unique Associations Among Emotion Dysregulation Dimensions and Aggressive Tendencies: A Multisite Study

Abstract: Although problems with emotion regulation (ER) have long been associated with internalizing symptoms, only recently has an ER framework been applied to the study of aggression. Therefore, little is known about the unique and independent associations between specific domains of the ER construct and different kinds of aggressive tendencies. We sought to explore these associations in two independent samples of young adults. Furthermore, we tested whether gender moderated the proposed emotion dysregulation-aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There is important variation in the degree to which psychopathic delinquents experience positive and negative emotional states, the degree to which they acknowledge, understand, and are aware of those emotional states, and the degree to which they can modulate, control, and regulate their emotional states. Much recent work has shown that salience of negative emotionality and its association with externalizing symptoms Velotti et al, 2017), which certainly tangents on the focus of the current study.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There is important variation in the degree to which psychopathic delinquents experience positive and negative emotional states, the degree to which they acknowledge, understand, and are aware of those emotional states, and the degree to which they can modulate, control, and regulate their emotional states. Much recent work has shown that salience of negative emotionality and its association with externalizing symptoms Velotti et al, 2017), which certainly tangents on the focus of the current study.…”
Section: Discussionmentioning
confidence: 72%
“…There is important variation in the degree to which psychopathic delinquents experience positive and negative emotional states, the degree to which they acknowledge, understand, and are aware of those emotional states, and the degree to which they can modulate, control, and regulate their emotional states. Much recent work has shown the salience of negative emotionality and its association with externalizing symptoms (Baglivio, Wolff, DeLisi, Vaughn, & Piquero, 2016;Velotti, Casselman, Garofalo, & McKenzie, 2017), which certainly tangents on the focus of the current study. Psychopathic delinquents that chronically experience negative emotions, especially sadness and depression, would likely be at greater risk for suicidal behaviors.…”
Section: Discussionmentioning
confidence: 75%
“…The possibility that emotion dysregulation may account for some of the shared variance between psychopathy and aggression is supported by burgeoning evidence that, in addition to being related to psychopathy, ER shows robust links with aggressive tendencies and behavior as well Roberton et al, 2014Roberton et al, , 2015Rogier et al, 2019;Shorey et al, 2011;Velotti et al, 2017). In short, recent studies have reported consistent and uniform associations between impairments in the ER domains and different components (e.g., anger, hostility) and forms (e.g., reactive, proactive) of aggression in community and offender samples.…”
Section: Emotion Dysregulation: Associations With Psychopathy and Aggressionmentioning
confidence: 99%
“…However, the extant literature on this topic frequently reports inconsistent results, failing to describe coherent gender differences in terms of emotion regulation within romantic relationships (Velotti, Casselman, Garofalo, & McKenzie, 2015; Velotti, Zavattini, & Garofalo, 2013). For example, a study conducted by Debrot et al (2012), aimed at investigating interpersonal emotion regulation processes within romantic relationships, highlighted only small and somewhat inconsistent gender differences between partners.…”
Section: Gender Differences In Emotion Regulationmentioning
confidence: 99%